Optical spectrum of HDE 245770 /A0535 + 26/ - R. A. Wade; J. B. Oke (The Astrophysical Journal, 1977)
Screening of methicillin-resistant/susceptible Staphylococcus aureus (MRSA/MSSA) is important for healthcare facilities to prevent hospital-acquired infections. The two common MRSA screening approaches are culture-based testing with selective and/or differential properties and nucleic acid amplification testing (NAAT). Both approaches have limitations. Here, we evaluate a novel culture-independent, antibody-based technology, the rapid detection-analysis platform (RDAP), to detect and differentiate MRSA and MSSA. A cohort of 64 clinical specimens was used to compare the RDAP with either culture using the chromogenic BBL CHROMagar MRSA II/CHROMagar SA bi-plate (30 specimens) or NAAT using the GeneXpert MRSA NxG (34 specimens) with a blinded design. Compared to culture, RDAP correctly detected 4/4 MRSA-positive samples, 2/2 MSSA-positive samples, and 19/24 S. aureus-negative specimens and had an overall agreement of 83.3% (25/30). Compared to NAAT, RDAP correctly identified 4/4 MRSA-positive samples and 28/30 MRSA-negative specimens and had an overall agreement of 94.1% (32/34). All nine discrepancies were false positives, which may be explained by RDAP having a lower limit of detection than the reference methods. The negative predictive values and test sensitivities were 100% for the RDAP compared to both reference approaches. Importantly, RDAP was able to detect and differentiate MRSA and MSSA with a turnaround time of 2.3 h, significantly shorter than the turnaround time of 24 h for culture. Taken together, RDAP can provide rapid results with a high negative predictive value to reduce unnecessary broad-spectrum antimicrobial use, minimizing the risk of resistance development, adverse effects, and costs.IMPORTANCEMethicillin-resistant Staphylococcus aureus (MRSA) and methicillin-susceptible Staphylococcus aureus (MSSA) are commonly encountered bacterial pathogens that lead to healthcare-associated infections and life-threatening conditions. Healthcare systems often implement active patient carriage screening programs to identify MRSA, and sometimes MSSA, using nucleic acid amplification testing or culture-based diagnostic approaches. Here, the rapid detection-analysis platform (RDAP), a novel bacterial detection approach, was evaluated for detecting and distinguishing MRSA and MSSA directly from clinical carriage nasal swab specimens. The RDAP approach offers promising results significantly faster than culture-based screening methods. The RDAP is a new technology to rapidly screen MRSA and MSSA to improve infection prevention practices and potentially aid in therapeutic decision-making.